Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left|3x-1\right|=\left|2x+5\right|\)
\(\Rightarrow\orbr{\begin{cases}3x-1=2x+5\\3x-1+2x+5=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}3x-2x=5+1\\5x+4=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=6\\x=-\frac{4}{5}\end{cases}}\)
Ta có: \(\hept{\begin{cases}\left(x-1\right)^2\ge0\\\left|3y-1\right|\ge0\\\left|z+2\right|\ge0\end{cases}}\Rightarrow\left(x-1\right)^2+\left|3y-1\right|+\left|z+2\right|\ge0\)
Dấu "="\(\Leftrightarrow\hept{\begin{cases}\left(x-1\right)^2=0\\\left|3y-1\right|=0\\\left|z+2\right|=0\end{cases}}\)
\(\Leftrightarrow\hept{\begin{cases}x-1=0\\3y-1=0\\x+2=0\end{cases}}\)
\(\Leftrightarrow\hept{\begin{cases}x=1\\y=\frac{1}{3}\\z=-2\end{cases}}\)
Vậy x = 1, \(y=\frac{1}{3}\),z = -2
b)\(\Leftrightarrow\left(2x-1\right)\left(x-4\right)\left(x-3\right)=0\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}2x-1=0\\x-3=0\\x-4=0\end{array}\right.\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=\frac{1}{2}\\x=3\\x=4\end{array}\right.\)
a) Xét \(x^3-5x^2-4x+40=0\)
\(x^2\left(x-5\right)-4x+20=-20\)
\(x^2\left(x-5\right)-4\left(x-5\right)=-20\)
\(\left(x^2-4\right)\left(x-5\right)=-20\)
Từ đó : suy ra \(x-5\inƯ\left(-20\right)=\left\{=\pm1;\pm2;\pm4;\pm5;\pm10;\pm20\right\}\)
Sau đó lập bảng để tính